Report of the Working Group on Empowering the Disabled for the Tenth Five Year Plan - Planning Commission (Planning Commission Government of India, 2001)
This document presents a comprehensive synthesis of the Working Group Report on Empowering Persons with Disabilities formulated for India’s Tenth Five-Year Plan (2002–2007). The report advocates a paradigm shift from welfare-oriented interventions to a rights-based framework that promotes full participation and social inclusion of persons with disabilities (PWDs) across all sectors of development. Central to the recommendations is the institutionalization of a Disability Sub-Plan, mandating that all government ministries earmark 5 percent of their budgets for disability-related initiatives, supported by a robust monitoring and accountability mechanism under the Planning Commission. The report emphasizes a holistic, life-cycle approach to rehabilitation, encompassing prevention, early identification, education, skill development, employment, and long-term social security. Inclusive education is identified as a critical pillar, with targeted investments in teacher training, accessible infrastructure, and specialized support for women and girls with disabilities. Vocational training, self-employment, and sector-specific opportunities—particularly in agriculture, dairy, and horticulture—are highlighted as key strategies for enhancing livelihood security, especially in rural areas. Further, the report underscores the importance of assistive technology development, creation of barrier-free physical environments, and expansion of community-based rehabilitation and outreach services. Special attention is given to the empowerment of women with disabilities through dedicated budget allocations, housing support, and research initiatives. Overall, the recommendations outline a coordinated, multi-sectoral framework aimed at mainstreaming disability concerns into national development planning, fostering equity, dignity, and sustainable inclusion of persons with disabilities in Indian society.
Government of India Planning Commission New Delhi June, 2001
Keywords: Empowerment of Persons with Disabilities; Tenth Five Year Plan; Disability Sub-Plan; Inclusive Education; Vocational Training; Employment Generation; Assistive Technology; Barrier-Free Environment; Community-Based Rehabilitation; Women with Disabilities; Monitoring and Evaluation; Rights-Based Approach